Experimental investigation of flow instabilities in a wide gap turbulent rotating Taylor-Couette flow. (September 2019) - Naseem, Umair; Awan, Muhammad Bilal; Saeed, Baber; Abbas, Naseem; Nawaz, Saad; Hussain, Muzamil
Abstract: In fluid sciences, flow between two cylinders has subtle industrial applications. This research has experimentally investigated the instabilities in a wide gap Taylor Couette flow with counter rotating cylinders of 0.1 radius ratio. Study has been done for various angular momentum ratios (λ) ranging from 0 → −3 at a constant cylinders' rotation difference (ΔΩ) of 2500 rpm and 3000 rpm. Two specific types of vortices have been observed during the flow visualization. The first vortex originated before the middle section with larger diameter of 2.31 cm, whereas the second one formed near the outer cylinder with 0.997 diameter. Probability distribution of vortex lifetime shows that the maximum lifetime probability of vortices is between 0.44 and 0.48 s. A relatively new behavior of vortices was observed. Vortices tend to travel in pairs and near the inner, high velocity cylinder vortices were cylindrical while at the outer slow velocity cylinder they were elliptical in the shape. It is observed that in turbulence range, increasing or decreasing the Reynolds number within certain limits does not have any significant effect on the shape of the flow structures. Particle Image Velocimetry (PIV) test shown almost similar results. Vector maps were calculated using Adaptive correlation method. The maximum velocity was in the range of 0.432–0.5 m/s and it occurred near the both cylinders wall. These observations will be helpful in future studies for analyzing the mixing, transport and drag properties of the fluid.